How Can Anesthesiologists Influence Policymaking? Reflections from a Year at the Council of Economic Advisers. (31st March 2021) - Sun, Eric C.
Abstract : From September 2019 to August 2020, the author served as a senior economist on the Council of Economic Advisers, a government agency charged with providing economic analysis and advice to the President of the United States and senior government officials. Working with the Council yielded many useful lessons on how anesthesiologists can influence healthcare policy. First, because the President has wide latitude over many areas of health policy that directly impact patient care and anesthesiologists' working environment, anesthesiologists should focus their efforts on influencing policymakers within the executive branch of government in addition to influencing lawmakers. Second, policymakers are busy and typically do not have a technical background, so anesthesiologists must learn how to communicate with them succinctly and at an appropriate level. Finally, because policymakers often need analysis quickly, anesthesiologists must meet these needs even if the underlying analysis is rougher and less precise that what would normally be needed for peer review. Abstract : Spending a year as a senior economist at the Council of Economic Advisers yielded many insights into the policymaking process and how anesthesiologists can influence policy.